THE EFFECT OF OVERCONFIDENCE AND MANAGEMENT ABILITY ON THE ISSUANCE OF THE AUDITOR'S REPORT CONSIDERING THE ISSUANCE OF CONTINUATION REPORT1 AND AUDITOR TENURE - Dr. Javad Reza Zadeh; Dr. Akeel Dakheel Kareem; Ali Farhan Murad (Scholar Express Journals, 2022)
There is an extensive literature on the factors that determine the audit fee and the auditors' willingness to publish a report containing the company’s continuity clause. However, much previous research has focused on firm-level determinants, and very little empirical evidence has been provided on the impact of owner management characteristics on payroll and auditor reporting. This study was conducted to investigate the effect of overconfidence and managerial power on the continuity of the company and the activities of the auditor. In the present study the applied in terms of purpose and according to the type of data and available analysis methods, the combined data method has been used. The method of data collection is the method of document mining and reference to databases and the method of data analysis is inferential. The research period is 2011 to 2020 and 90 companies have been selected as the final sample of the research. The results show that excessive management trust has a significant impact on business continuity. It was also observed that management ability significantly moderates the relationship between management overconfidence and continuity of activity. In addition, the results showed that management overconfidence has a significant effect on the auditor's tenure and, finally, management ability significantly moderates the relationship between management overconfidence and auditor tenure. The results of the research showed that the overconfidence of the management had a significant impact on the business continuity of the companies. The research results showed that management ability significantly moderates the relationship between management overconfidence and business continuity. The results of the research showed that overconfidence of the management had a significant effect on the tenure of the auditor. The research results showed that management ability significantly moderates the relationship between management overconfidence and auditor tenure.
Keywords: Overconfidence and management ability; auditor's decision; issue a continuation report